Стратегії суб'єктного позиціонування в англомовному блог-дискурсі - Шкамарда, Оксана Андріївна; Shkamarda, Oksana A. (Видавництво Національного університету "Острозька академія", 2015)
У статті розкрито специфіку позиціонувальних стратегій на прикладі англомовного персонального блогу “In Pursuit of Happiness”. Проведений аналіз авторських онлайн повідомлень дав змогу виокремити дискурсивні механізми актуалізації глобальної, локальних та мовленнєвих стратегій суб’єктного позиціонування в комунікативному середовищі Інтернет-блогу. У роботі дано визначення поняттям «блог-дискурсу» та «позиції суб’єкта дискурсивної діяльності». The article focuses on the discursive strategies of subject positioning in the English Internet blog. The material of the research is based on the written messages of the personal blog “In Pursuit of Happiness”. Blogs, which are seen as online journals, allow users to reflect and share opinions as well as discuss various topics. In other words, they offer moden opportunities for stancetaking and identification over the Internet. Stance is treated in this work as an interactional phenomenon that consists of epistemic and affective elements and includes subjective expressions of the speaker’s attitude towards the object of conversation, including marking of his / her mood, evaluations, perspective, point of view and opinion. It has been proved that bloggers use certain discursive strategies to construct their stances. Subjective positioning strategy in the Internet blog is defined as a cognitive model that modifies the stancetaker’s discursive behavior, implements his / her intentions and influences on the recepient’s cognition and emotions. It has been shown that positioning strategies in the personal blog are divided into global, local and speech strategies. Some of the linguistic resources (lexical, grammatical and stylistic) which the speakers have at their disposal for articulating a stance have been examined in this article.
Strategies of subjective positioning in the english blog discourse
Keywords: суб’єкт дискурсивної діяльності; позиціонування; блог-дискурс; глобальна стратегія; локальна стратегія; мовленнєва стратегія; subject of discourse; positioning; blog discourse; global strategy; local strategy; speech strategy